5 - Donner un sens au nom du festival de la ville Les enjeux de la reconstruction des liens d’appartenance dans une ville tunisienne naissante - Mouldi Lahmar, (African Sociological Review, 2015)
The purpose of this paper is to analyze, from the observation of a local festival , the multiple challenges of rebuilding the bonds of belonging to the rural population , who are engaged - from due to their recent urbanization - in a process of restructuring and renegotiation of these links and their corresponding representations . The conflicts that have accompanied and currently accompany the process described are sometimes expressed in terms of community identity struggles, mobilizing rural , while the issue is largely about access and membership in small urban space training.